Development of A Multidimensional Assessment Instrument on the Topic of Torque - Lola Ananda; Pujianto; Edi Istiyono (Jurnal Penelitian Pembelajaran Fisika, 2025)
This research focuses on the development of a multidimensional assessment instrument aimed at evaluating high school students’ learning outcomes in the topic of torque within physics education. The instrument integrates cognitive, affective, and psychomotor domains through a combination of multiple-choice questions for conceptual understanding and Likert-scale questionnaires for assessing students’ interest and communication skills. The development process followed a systematic model consisting of planning, instrument construction, and pilot testing. The trial was conducted with 22 eleventh-grade students from SMAN 1 Dlingo, Bantul, Indonesia, selected via random sampling. Content validity was assessed using Aiken’s V index, while internal consistency reliability was measured using Cronbach’s Alpha with SPSS version 26.0. The results indicated that all items demonstrated high content validity (V > 0.87) and acceptable to excellent reliability coefficients: 0.74 for cognitive, 0.81 for affective, and 0.93 for psychomotor components. These findings affirm that the developed instrument is both valid and reliable, making it suitable for comprehensive evaluation of student learning outcomes in physics. Practically, the instrument enables teachers to diagnose students’ conceptual mastery, motivation, and communication skills in an integrated manner, especially for abstract topics like torque. The novelty of this research lies in its multidomain assessment design tailored to the challenges of physics learning in the Indonesian high school context, supporting differentiated instruction and holistic evaluation aligned with the curriculum.